Role of Kalla Group in Collaborative Governance Implementation of Covid-19 Management in Makassar City - Muhammad Yusran Amir; Moh Thahir Haning; Nurdin Nara; Muhammad Yunus; Muh. Akmal Ibrahim; Gita Susanti; Badu Achmadi (Media Publikasi Cendekia Indonesia, 2022)
This research is to analyze the dynamics of collaboration, and collaborative actions of the Kalla Group with the Makassar city government in tackling COVID-19. This research method is qualitative research that focuses on examining the phenomena that occur in the dynamics of collaboration, and collaborative actions between the government and the private sector in the implementation of the COVID-19 response in Makassar City. Data collection techniques were carried out through in-depth interviews, observation and document review, namely collecting and studying relevant data and supporting research, literature, lecture materials, expert theories, and documents or archives that support this research. The informants from this study were 6 key informants selected purposively. The results of the study show that the Kalla Group has very good collaboration with the Makassar City Government in tackling COVID-19 in Makassar city. The role of the Kalla Group is in 2 stages, namely 1) Collaborative Dynamics, and 2) Collaborative Actions. There are 3 aspects in the dynamics of collaboration, namely the mobilization of shared principles, building shared motivation, and the capacity to take joint action. The Kalla Group carries out various collaborative actions so as to have an impact on the health, economy, and education sectors. The conclusion is that the Kalla Group Company has very good collaboration in Collaborative Governance for handling COVID-19 with the City Government of Makassar.